A New Procedure for Assessing the Sensitivity of Antennas Using the Unscented Transform - de Menezes, L.R.A.X.; Soares, A.J.M.; Silva, F.C.; Terada, M.A.B.; Correia, D. (IEEE transactions on antennas and propagation, 2010)
In this communication, we introduce a new procedure to analyze the sensitivity of antennas. The procedure is based on the method of unscented transform (UT) developed by Julier and Uhlman in 1997. Although the UT is used in control engineering, the method has only recently been applied to electromagnetic (EM) problems. This work describes the application of the UT both for single and multiple random variables cases. The UT method is applied to problems using examples involving different types of antennas. In each example, the UT method is combined with different numerical methods to perform the sensitivity analysis of wire or reflector antennas. In the first example, the results were validated with results from the Monte Carlo technique. The second example investigated the convergence of the UT procedure, and the final example compared UT results with measured data. The main conclusion is that UT is a feasible alternative to the popular Monte Carlo technique, with the advantage of being far less computationally expensive.